THE EFFECT OF VINE LOAD ON THE YIELD OF RIZAMAT GRAPES - Malikov Azim Nematovich; Uralov Shermamat; Suvonkulova Iroda Ahmad qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Viticulture is one of the oldest profitable branches of agriculture in the country. Favorable natural and climatic conditions of Uzbekistan allow growing grapes at different times, ie the earliest and the latest. Grapes are used for various purposes (consumption, processing, etc.). Grapes are consumed fresh from July to November. Stored in special refrigerators, they can be consumed in March-April as a delicious and medicinal fruit. Fresh grapes are also used to make jams, compotes, juices, molasses, concentrates, high-quality wines. Raisin varieties give a very nutritious, healing product when dried. Raisins (raisins, harmonies, etc.) have long been valued as a nutritious and healing food and have a dietary property. Grapes contain up to 80% sugar, mainly glucose and fructose.